The Relationship Between Age And Parity Of Laboring Mothers With The Incidence Of Low Birth Weight (LBW) At Arjawinangun Hospital - Eva Fauziah (Jurnal EduHealth, 2024)
The incidence of low birth weight (LBW) needs to be prevented because it is one of the causes of death that contributes to increasing the infant mortality rate (IMR). Several factors of LBW need to be assessed and researched including maternal age and parity. From the results of the study at Arjawinangun Hospital, it was found that the number of delivery services in the VK Room was 1793 mothers, 179 LBW babies, 8 maternal deaths and only 1 IMR due to asphyxia. This study aims to relate the age and parity of laboring mothers with the incidence of Low Birth Weight (LBW) at Arjawinangun Hospital. The research method used quantitative research with a cross sectional approach. The population was 1,793 babies with a sample size of 95 babies with simple random sampling technique. The data collection used secondary data in the form of medical records and the data analysis used the chi square test at α = 0.05. The results showed that out of 95 respondents (51.6%) babies at Arjawinangun Hospital had LBW, the age of the laboring mother was 20-35 years (41.1%) and the parity of the laboring mother was multipara (52.6%). There is a relationship between age (r value = 0.000) and parity (rvalue = 0.045) with the incidence of low birth weight (LBW) at Arjawinangun Hospital, Cirebon Regency.